Evaluación de la producción invitro de embriones en animales domésticos en el laboratorio de biotecnología de la reproducción en la carrera de medicina veterinaria de la Universidad Técnica de Cotopaxi - Salguero León, Nuvia Viviana (2014)
The present research was carried out in the Biotechnology Reproduction laboratory of the Veterinary Medicine and Zootechnics Faculty at Technical University of Cotopaxi. The main objective of the present research was to evaluate canine embryos for a reproduction In Vitro. It is a technique that the veterinary medicine has in order to help the fertility process treatment, allowing to improve the pet breeding. It is useful and effort, Knowing that through well-established embryos and constant transference could increase the production of superior genetic, as long as there are series of important factors for good results that can be discussed later. To carry out the research, it was considered as the beginning the collected oocytes. From this result, how many matured and how many did not mature, which are called atretics, and from matured oocytes how many were fertilized and finally, as a result which quality embryos could be accomplished.